Does 25 cents more per day make a difference? The impact of livestock transfer and development in rural Zambia. (August 2016) - Kafle, Kashi; Winter-Nelson, Alex; Goldsmith, Peter
Highlights: Field experiment to assess the impact of a livestock transfer program in Zambia Significant growth in expenditure, small in absolute value – $0.25/day per person. Small absolute change triggers a big qualitative change in the composition of diet. Shift from staple to nutritious foods and enhanced feeling of economic security. Changes in composition of consumption vary with the type of livestock transferred. Abstract: Analyses of the impacts of asset transfer programs often find statistically significant effects on consumption expenditures that are large in percentage terms but small in absolute value. This study explores the practical significance of such impacts using the case of a livestock transfer program among impoverished households in Zambia. As in other studies, results show that the asset transfers increased household consumption expenditure and dietary diversity. Extending previous work, this paper examines whether the increase in expenditures has been large enough to trigger changes in consumption patterns or in subjective assessment of poverty status. Changes in composition of expenditures, composition of diet, and subjective self-assessment of poverty all suggest a growing sense of security and a practically significant change in welfare for treated households. As transfers included three different types of animals – dairy cows, meat goats, and draft cattle – we are able to discern that the specific nature of the asset transferred influences food security impacts. Examination of change in the composition of consumption shows substantial effects on poverty and food security starting within six months of livestock transfers. Persistence of the impact through the next 18 months of our study period indicates that livestock transfers can have a sustained effect on poverty and food security.